Do Executive Incentives Drive Performance? A Study of Manufacturing Firms in Indonesian - Chandra, Budi; Mardianto, Mardianto; Krisyadi, Robby; Christina, Claudia (Fakultas Teknik dan Ilmu Komputer, Universitas Sains Al-Qur'an (UNSIQ) Wonosobo, 2026)
The growing disparity between executive compensation (EXECOMP) and employee wages, along with increasing concerns over the effectiveness of incentive structures, highlights the urgency of understanding how executive pay influences firm performance (FP). This study investigates whether well-aligned compensation schemes can effectively motivate executives and enhance firm value, particularly under conditions of public scrutiny and regulatory pressure. Grounded in agency theory, the study analyzes 264 observations from manufacturing firms listed on the Indonesia Stock Exchange (IDX) between 2016 and 2022. Using Ordinary Least Squares (OLS) regression analysis, the results reveal a statistically significant positive relationship between EXECOMP and FP. These findings underscore the importance of performance-based incentives in driving executive behavior and improving financial outcomes. The study contributes to the literature by offering updated empirical evidence from an emerging market context, reinforcing the strategic role of EXECOMP in promoting sustainable corporate growth.